War Narratives Through The Eyes/I´S of Women in Iman Humaydan Younes’ B As In Beirut - Azar, Daisy Waked (European Scientific Journal, ESJ, 2018)
Lebanese author and journalist Iman Humaydan Younes published her debut novel B as in Beirut in Arabic in 1997 while the English translation didn’t appear until 2007. The novel is divided into four narratives told by Lillian, Warda, Camilia, and Maha who live in the same apartment building in Beirut during the Lebanese civil war that extended from 1975 till 1990. Younes chooses to present personal narratives that reflect the emotional states of these women rather than describe the violent occurrences of the actual war. In this sense she tells of the repercussions of the war on her female narrators, and the coping mechanisms that each adopts away from the violence, destruction and absurdity that have been the main foci of most Lebanese war novels. My paper affects a close reading of these interlocked narratives and investigates the female voices behind them: who they are, what they are going through, and what they do in order to survive the state of inertia and loss during the civil war. My contention is that Younes’s novel is one of the very few that succeeds in conveying the female experience during the civil war and paves the way for a Feminist attitude towards gender roles in a war- torn nation, and towards an understanding of the place of the woman in an overly maleoriented and maneuvered dominion.